2010
DOI: 10.1007/s10633-010-9213-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between functional and anatomical assessments by multifocal electroretinography and optical coherence tomography in central serous chorioretinopathy

Abstract: To evaluate the correlation between functional and anatomical assessments with multifocal electroretinography (mfERG) and optical coherence tomography (OCT) in patients with acute central serous chorioretinopathy (CSC). Thirty-four eyes of 34 patients with acute CSC underwent mfERG and OCT examinations. First-order mfERG N1 and P1 response amplitudes and latencies were analyzed.OCT parameters measured included central subretinal fluid (SRF) thickness, central retinal thickness, total central foveal thickness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 19 publications
2
26
1
1
Order By: Relevance
“…However, we found that neither total central retinal thickness nor central neurosensory retinal thickness was correlated with baseline or final BCVA. This is in concordance with findings of Yip et al [30], who found no correlation between BCVA and both central retinal and total central foveal thickness in acute CSR patients [30]. Additionally, Yip et al [30] found no correlation between BCVA and horizontal and vertical diameters of SRF, as did we.…”
Section: Discussionsupporting
confidence: 93%
“…However, we found that neither total central retinal thickness nor central neurosensory retinal thickness was correlated with baseline or final BCVA. This is in concordance with findings of Yip et al [30], who found no correlation between BCVA and both central retinal and total central foveal thickness in acute CSR patients [30]. Additionally, Yip et al [30] found no correlation between BCVA and horizontal and vertical diameters of SRF, as did we.…”
Section: Discussionsupporting
confidence: 93%
“…However, no significant correlation was observed between the mfERG and any of the retinal thickness measured with OCT. Comparably, Yip et al reported no significant correlation between the mfERG of various rings and the OCT parameters in eyes with central serous chorioretinopathy 36. These findings demonstrate that functional assessment using mfERG better reflects the level of VA, and not anatomical evaluation by OCT.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, the visual acuity and the retinal response density of the foveal area (ring 1) seemed to have little relationship with the foveal thickness. Yip and colleagues reported no significant correlation between the mfERGs of various rings and the OCT parameters in eyes with central serous chorioretinopathy 15 . Also, no significant correlation was observed between the logMAR visual acuity and any of the OCT measurements.…”
Section: Discussionmentioning
confidence: 98%
“…This may be explained by the fact that macular oedema is only one parameter that can affect visual acuity and the electrical activity of the macula. There are other possible factors that can affect macular function, including the chronicity of the disease, composition of sub‐retinal fluid and pre‐existing photoreceptor damage 15,17 …”
Section: Discussionmentioning
confidence: 99%